Legal Discoveries in the Digital Age: Challenges in Interpreting New Technology Regulations in Indonesia - Khofifah Hasanah Pane; Daniel Lodewijk Peter; Febrian Rizky Akbar; Irwan Triadi (Journal of Political and Governance Studies, 2025)
Background The rapid evolution of digital technology has generated new legal challenges that remain insufficiently addressed within Indonesia’s positive law. This regulatory lag creates normative gaps, making judicial legal discovery increasingly essential in resolving disputes related to digital innovation. This study aims to examine how judges interpret and apply the law when confronting cases involving electronic transactions, artificial intelligence, data protection, and digital assets. Methods Using a normative juridical method, the research analyzes relevant literature, legal doctrines, and court decisions to identify patterns of judicial reasoning in situations where statutory provisions are unclear or absent. Results The findings reveal that traditional interpretive techniques are often inadequate to address the complexity and technical nature of digital phenomena. Judges frequently struggle to align existing norms with emerging technologies, and limited technological literacy among legal actors contributes to inconsistent rulings and heightened legal uncertainty. Conclusion The study concludes that Indonesia requires more adaptive judicial methodologies and timely regulatory reforms to ensure legal certainty, fairness, and utility in the digital era. A progressive interpretive approach is vital to prevent the legal system.